BEHAVIOUR FINANCE STUDENT RECIPIENTS OF THE SMART INDONESIA CARD SCHOLARSHIP (KARTU INDONESIA PINTAR-KIP) - Dharmayasa, I Putu Arya; Irwansyah, M. Rudi (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to find out how Locus of Control on students' personal financial management behavior and financial literacy on students' personal financial management behavior. This research was conducted on students of the Faculty of Economics Universitas Pendidikan Ganesha with a population of 398, after calculations were carried out, 199 students were used as research samples. The data collection method uses a questionnaire, while the data analysis technique uses quantitative descriptive analysis techniques. Based on the results of data analysis, it was found that there was an influence between Locus of Control and financial literacy on students' personal financial management behavior. This shows that the increasing locus of control and knowledge of students' financial literacy will increase students' ability to manage their finances.